OP83 Adverse childhood experience and health service utilisation: findings from a primary care-based study. (31st August 2015) - Mellon, L; McHugh, SM; Sinnott, C; Kearney, PM
Abstract : Background: Research has shown that those who have experienced adverse childhood events (ACE) are at increased risk of developing chronic diseases later in life. The relationship between ACE and health service use (HSU) is subject to potential confounding factors including those chronic diseases. Existing evidence is largely based on hospital administrative data, limiting the investigation of other influential predisposing, enabling and need factors. Our aim was to examine the association between ACE and HSU using data from a primary care-based survey. Methods: We analysed cross-sectional data from the Mitchelstown study, a population based cohort of people aged 50 to 69 recruited from a large primary care centre (2010/2011). ACE was measured by self-report using the Centre for Disease Control ACE questionnaire. Health service use in the previous 12 months (number of GP consultations and hospital discharges) was extracted from electronic medical records. Negative binomial regression was conducted, adjusting for predisposing (age, sex), enabling (education, social class, having a medical card entitling holder to free GP care) and need factors (multimorbidity: 0, 1 or ≥2 chronic diseases), using Stata 12. Results: HSU data were available on 2026 participants (99% of total sample = 2047), 1885 of whom completed the ACE questionnaire. Overall, 23.4% ( n = 4 41, 95% CI: 21–25%) reported a history of ACE. Adjusting for age, sex, education, social class and medical card status, a history of ACE was significantly associated with a higher number of GP consultations (incidence rate ratio, IRR = 1.2, p < 0 0.001; 95% CI 1.0–1.3). However, the association was not significant when multimorbidity was included in the model (IRR = 1.1, p > 0 .05, 95% CI: 1.0–1.2). Significant factors included having a medical card (IRR = 1.92, 95% CI: 1.7–2.1), multimorbidity (IRR = 1.9, 95% CI: 1.7–2.2) and third level education (IRR = 0.8. 96% CI = 0.7–0.9). ACE was not significantly associated with number of hospital discharges (IRR = 1.5, p = 0 .124, 95% CI: 0.9–2.5). Discussion: Adverse childhood experience has been conceptualised as a need factor which may influence health service utilisation. Our results suggest that the impact of ACE on the frequency of GP consultations may be mediated through enabling factors such as free access to services and other need factors such as multimorbidity.